ANALYSIS OF TECHNOLOGICAL INDICATORS OF TWO-LAYER KNITTED FABRICS OF THE NEW STRUCTURE (European Journal of Interdisciplinary Research and Development, 2022)
In this article, 5 samples of two-layer knitted fabric with a new structure were woven on a Mayer knitting machine and its technological parameters were analyzed.